DAMS - ESTHER DUFLO AND ROHINI PANDE (The Quarterly Journal of Economics, May 2007, 2007)
This paper studies the productivity and distributional effects of large irrigation dams in India. Our instrumental variable estimates exploit the fact that river gradient affects a district's suitability for dams. In districts located downstream from a dam, agricultural production increases, and vulnerability to rainfall shocks declines. In contrast, agricultural production shows an insignificant increase in the district where the dam is located but its volatility increases. Rural poverty declines in downstream districts but increases in the district where the dam is built, suggesting that neither markets nor state institutions have alleviated the adverse distributional impacts of dam construction